Acridine orange as a coreactant for efficient electrogenerated chemiluminescence of tris(2, 2′-bipyridine)ruthenium(ii) and its use in selective and sensitive detection of thiourea. Issue 38 (7th April 2020) - Saqib, Muhammad; Bashir, Shahida; Kitte, Shimeles Addisu; Li, Haijuan; Jin, Yongdong
Abstract : We introduced a novel coreactant for efficient anodic electrochemiluminescence of Ru(bpy)3 2+ and applied it for the sensitive detection of thiourea for the first time. Abstract : A new and efficient anodic Ru(bpy)3 2+ ECL system by using acridine orange (3, 6-Bis(dimethylamino)acridine, AO) as a coreactant was reported in a neutral medium. The developed Ru(bpy)3 2+ –AO system displayed a higher ECL intensity than that of the classic Ru(bpy)3 2+ – oxalate ECL system, and was further exploited for the ECL detection of thiourea for the first time.